The Effect Of Pentagon Fraud Components On Indications Of Financial Statement Fraud - Rifat, Ahmad; Ahmar, Nurmala; Mulyadi, JMV. (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2024)
The purpose of this research is to examine and analyse the influence of pentagon fraud components (pressure, opportunity, rationalisation, competence, and arrogance) on financial statement fraud. The samples used in this study are 90 manufactured companies that were listed on the Indonesia Stock Exchange during the period 2017-2019. The type of data used is secondary data, in the form of annual reports of companies listed on the Indonesia Stock Exchange during the period 2017–2019. Hypothesis testing was conducted with PLS (Partial Least Squares) software. The result showed that opportunity (receivable), rationalisation (TACC), and competence (DIRCHANGE) had an effect on the financial statement fraud. While pressure (ACHANGE) and arrogance (CEO PIC) had no effect on financial statement fraud.